Stress-related psychological factors for back pain among athletes: Important topic with scarce evidence - Heidari, J.; Hasenbring, M.; Kleinert, J.; Kellmann, M. (European Journal of Sport Science, 2017)
Health issues represent a frequent problem for athletes, as this particular demographic is repeatedly confronted with physically and psychologically stressful situations. Back pain (BP) materialises as comparatively common health problem being regarded as functionally limiting and psychologically straining burden for athletes. According to research conducted on athletes with BP, biomechanical and physiological mechanisms emerge as influential, whereas stress-related psychological factors appear to be neglected. For athletic injuries, the essential impact of psychological processes on injury occurrence and return from injury has already been corroborated. Hence, the aim of this literature review is to: (1) introduce a conceptual differentiation between injuries and BP; (2) summarise the results obtained regarding stress-related psychological aspects for injuries; and (3) connect the injury research to the state-of-the-art evidence regarding stress-related factors for BP among athletes. A distinction between injuries and BP could be established based on previous definitions, despite the fact that a considerable overlap between both concepts prevails. Injuries can be attributed to a physical origin, whereas BP frequently lacks this physical criterion. For BP, our enquiry yielded four studies including psychological measures of stress - with two studies specifically examining the association between BP and psychological stress among athletes longitudinally. Abundant findings from the general population support the importance of considering psychological and specifically stress-related factors in BP prevention and rehabilitation, but evidence related to the athletic field remains elusive. Further scientific investigations with a wider methodological approach are needed to deepen the knowledge about the crucial relationship between psychological stress, BP, and athletes.